Understanding Change in Complex Health Systems -a review of the literature on change management and social care 2007 - 2017 - Barry, Sarah; Eustace-Cook, Jessica (My University, 2018)
A review of the change management literature underpinning the Health Services Executive (HSE) formal Change Guide, People's Needs Defining Change - Health Services Change Guide (2018) Organisation Development and Design, Human Resources Division, HSE
PUBLISHED
Keywords: Inclusive Society; Making Ireland; CHANGE; Development; Health; Policy